Retinal microvascular complications during retrograde cerebral perfusion for aortic dissection surgery - (:unkn) unknown (My University, 2009)
The aim of this study was to determine the influence of retrograde perfusion on retinal microcirculation for aortic dissection surgery. The groups with a total number of 40 patients are composed as ascending aortic and arch replacement (Group II = 20) or the ascending aortic replacement only (Group I = 20). There were 25 men and 15 women (mean age 49.4 ± 13.5). The intimal tear was resected and replaced with a Dacron graft. All patients underwent fundus examinations on the first day and 4 weeks after operation. Ocular complications were detected in 20 patients (5 in Group I and 15 Group II). Blurring of vision was found in 15 and retinal pale in 5. Binocular photopsia was persisted in 6 patients after 4 weeks (all in Group II). The prevalence of transient ocular dysfunction was found significantly higher in the Group II. The ischemic lesions in the retina disappeared and no abnormality was observed by retinal angiography 6 months later. The ophthalmic observation is a useful method to determine the effectiveness of the cerebral perfusion directly during aortic dissection surgery. © 2009 Informa UK Ltd.
Keywords: Aortic dissection; Retinal ischemia; Retinal microcirculation; Retrograde cerebral perfusion